The creation and destruction of social capital : entrepreneurship, co-operative movements, and institutions - Svendsen, Gunnar Lind Haase, 1965-; Svendsen, Gert Tinggaard, 1963- (Cheltenham, UK ; Northhampton, MA : Edward Elgar, 2004)
The book attempt to bridge the gap between theory and reality by examining the main factors that determine entrepreneurship, co-operative movements and the creation and destruction of social capital.
Includes bibliographical references (p. 183-200) and index.
Keywords: Cooperation; Social capital (Sociology); Entrepreneurship; Cooperation -- Denmark; Cooperation -- Poland